Design of Blue-Green Infrastructure Network in Kigali, Rwanda: A Case Study of the Green City Kigali Project on Kinyinya Hill - Wantzin,Hanna; Blackert,Anna (TVVR 5000, 2025)
Rising global temperatures are disrupting the natural hydrological cycle, leading to both increased frequency and severity of flooding events, as well as prolonged periods of water scarcity. In Kigali, Rwanda, these shifts pose substantial challenges to urban development and public safety. In response, the Government of Rwanda is pursuing further development of Kigali through the Green City Kigali project, which aims to establish a climate-resilient urban community in the Kinyinya Hill area of the Gasabo district. In alignment with the project’s existing Master Plan, this study proposes a design for a blue-green infrastructure (BGI) network within the designated project area. BGI refers to a system of natural and semi-natural solutions intended to manage stormwater while simultaneously enhancing environmental quality and delivering multiple ecosystem services. Through a combination of literature review, semi- structured interviews and quantitative analysis, the study identifies appropriate BGI strategies and considers how local environment and social conditions can inform the design process. The proposed design incorporates elements such as detention basins, vegetated swales, culverts and other non-structural features to manage stormwater and support sustainable urban development.
Keywords: Blue-green infrastructure; Stormwater management; Multifunctional values; Climate resilience; Sustainability; Urban flooding